A comparative study on the combustion and emissions of a non-road common rail diesel engine fueled with primary alcohol fuels (methanol, ethanol, and n-butanol)/diesel dual fuel. (15th April 2020) - Ning, Le; Duan, Qimeng; Chen, Zhanming; Kou, Hailiang; Liu, Bing; Yang, Bo; Zeng, Ke
Highlights: Adding primary alcohol fuels increased the ignition delay and reduced the combustion duration. BTE was decreased, CO and PM emissions were reduced, and THC and NOX emissions were increased by adding primary alcohol fuel. For a fixed ASP, methanol has the lowest COVIMEP and ringing intensity, and the highest BTE among the three alcohol fuels. Adding methanol produces the highest THC emission and the lowest CO, NOX and soot emissions among the three alcohol fuels. Abstract: Primary alcohol fuels are the most promising fuels for diesel engines, thanks to their low emissions and easy adaptability to engine technologies. In this paper, the effects of the addition of methanol, ethanol, and n-butanol on the combustion characteristics and performance of a common rail dual fuel engine with diesel direct injection and alcohol fuel port injection are examined, followed by a comparative analysis of the test results. The test engine was operated at the maximum torque speed of 2500 rpm, and with a mean effective pressure (IMEP) of 0.75 MPa. The engine performance was analyzed for different alcohol/diesel fuel mixtures by using five alcohol substitute percentages (ASPs): 0% (pure diesel), 10%, 20%, 30%, and 40%. The experimental results demonstrate that slower flame development and faster flame propagation can be obtained by mixing any of the three alcohol fuels with diesel, compared with the pure diesel. With an increased ASP, the coefficient of variation of IMEP (COVIMEP ) and the brake thermal efficiency (BTE) decreased, and the ringing intensity (RI) first increased and then dropped. The addition of primary alcohol fuels in the dual-fuel mode can also increase the total hydrocarbon (THC) and nitrogen oxide (NOX ) emissions, but the carbon monoxide (CO) and soot emissions decrease. The comparative analysis indicated that the addition of methanol has the lowest COVIMEP and RI and the highest BTE among the three alcohol fuels. Adding methanol produces the lowest CO, NOX, and soot emissions and the highest THC emissions among the three alcohol fuels.